Vibrational excitation induced by electron beam and cosmic rays in normal and superconductive aluminum bars - Bassan, M; Buonomo, B; Cavallari, G; Coccia, E; D'Antonio, S; Fafone, V; Foggetta, L; Ligi, C; Marini, A; Mazzitelli, G; Modestino, G; Pizzella, G; et al. (2011)
We report new measurements of the acoustic excitation of an Al5056 superconductive bar when hit by an electron beam, in a previously unexplored temperature range, down to 0.35 K. These data, analyzed together with previous results of the RAP experiment obtained for T > 0.54 K, show a vibrational response enhanced by a factor 4.9 with respect to that measured in the normal state. This enhancement explains the anomalous large signals due to cosmic rays previously detected in the NAUTILUS gravitational wave detector.